A Systematic Evaluation and Implementation Review of Non-Formal Education: Sewing Training for Life Skills Development - Imam Roos Wahyudi; Fakhruddin Fakhruddin; Mintarsih Arbarini; Yudi Siswanto; Sachin Gupta (Edukasi, 2026)
This study presents a systematic implementation review and program evaluation of a non-formal sewing training initiative conducted by SKB Kota Semarang, aiming to enhance life skills and economic independence among community members. The research focuses on two main aspects: (1) the instructional design of the sewing training program, and (2) its effectiveness based on the Context, Input, Process, and Product (CIPP) evaluation model. The sewing training was designed using a Competency-Based Training (CBT) approach aligned with the Indonesian National Work Competency Standards (SKKNI). The curriculum includes progressive modules from basic to advanced garment-making techniques, supported by 260 instructional hours, real-world practice using customer orders, and entrepreneurship components. Instructional delivery integrates demonstrations, peer learning, individual mentoring, and flexible scheduling to accommodate diverse learner needs. A qualitative descriptive method was employed, involving document analysis, classroom observations, and interviews with a coordinator, tutor, group leader, and participants. Findings show that the program aligns with learners' needs and goals, supported by competent instructors, sufficient funding (APBN), and appropriate infrastructure. The training process encouraged active participation and practical engagement, resulting in measurable skill acquisition and enhanced self-confidence. Despite these strengths, the program experienced a recent decline in enrollment due to limited promotion, scheduling rigidity, insufficient equipment, and lack of post-training support. These findings indicate the importance of strategic program enhancement to ensure sustainability and impact. The study concludes that the CIPP model offers a comprehensive framework not only to assess program effectiveness but also to guide continuous improvements in non-formal vocational education. This study contributes to the field of educational evaluation by applying the CIPP model to a community-based, non-formal vocational training program in Indonesia. It offers a structured and contextual analysis of program strengths and weaknesses, providing actionable insights for policymakers and educators. The study’s novelty lies in its holistic assessment of a grassroots educational initiative that integrates life skills development with local economic empowerment, a domain that is often overlooked in formal academic evaluations. By highlighting the intersection of education, gender, and community development, this research adds significant value to the discourse on non-formal education’s role in social transformation.